Relapsed/refractory acute myeloid leukemia: any progress? - Schlenk, Richard Friedrich; Müller-Tidow, Carsten; Benner, Axel; Kieser, Meinhard (Current opinion in oncology, 2017)
Aim of this review was to focus on prognostic and predictive factors, standard and new treatment approaches, and on statistical considerations for future clinical trials in patients with relapsed/refractory acute myeloid leukemia (r/r-AML). New prognostic molecular markers were identified in r/r-AML, FLT3-ITD, mutated IDH1, and biallelic CEBPA mutations. Intensive combination chemotherapy including gemtuzumab ozogamicin emerged as an effective salvage therapy in refractory AML. Timing of allo-HCT in r/r-AML may be oriented at the probability to achieve a response to intensive salvage therapy. Several new treatment approaches ranging from new and modified cytotoxic drugs to targeted approaches are in clinical development with first efficacy assessment in single-arm phase II studies. Their external validity may be considerably increased by using a novel design based on a matching approach. FLT3-ITD, mutated IDH1, and biallelic CEBPA mutations are identified as prognostic molecular markers in r/r-AML. Timing of allo-HCT should be based on the probability to achieve a response to intensive salvage therapy. Several new approaches are currently evaluated and matching for controls may help to increase external validity.